3D Printed Magnetic Origami Scaffolds for Guided Tissue Assembly - Brandon Daul; Ryan Martin; Phillip Glass; Reza Moonesi Rad; Richard Inho Joh; Fanben Meng; Daeha Joung (Advanced Materials Interfaces)
Abstract A 3D‐printed origami‐inspired magnetic scaffold has been developed to investigate the influence of physical cues on guided cellular proliferation in a 3D microenvironment. Microscale channels are first constructed and populated with NIH/3T3 fibroblast and/or A549 cancer cell clusters that are initially bioprinted within the channels. Once these channels are fully populated, a permanent magnet is applied to fold the scaffolds. By varying the channel width and incorporating an intermediate extracellular matrix hydrogel (IE) layer along with origami folding, the scaffold provides geometric and gravitational cues to influence cellular proliferation. In both monoculture and coculture, i) cells tend to proliferate more in a tapered manner, ii) scaffolds with enhanced media flow lead to a higher volume of cell growth, and iii) cells form homogeneous distributions under gravity after dispersion. In coculture, the expansion of fibroblast clusters within their seeded channels increased, facilitating the proliferation of cancer cell clusters into the non‐seeded channels. This origami scaffold offers valuable insights into tissue engineering and cancer research, serving as a versatile tool for examining cellular interactions and growth dynamics.